2019
DOI: 10.1007/s40333-019-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use and cover change on surface wind speed in China

Abstract: The surface wind speed (SWS) is affected by both large-scale circulation and land use and cover change (LUCC). In China, most studies have considered the effect of large-scale circulation rather than LUCC on SWS. In this study, we evaluated the effects of LUCC on the SWS decrease during 1979-2015 over China using the observation minus reanalysis (OMR) method. There were two key findings: (1) Observed wind speed declined significantly at a rate of 0.0112 m/(s•a), whereas ERA-Interim, which can only capture the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…By design, reanalysis products do not include in their hindcasting the changes in surface roughness (Thorne and Vose, 2010). Increase of surface roughness can be associated with factors such as urbanization, growth of forests, changes in trees and forest distribution or changes in agricultural practices (Yupeng et al, 2019). Previous studies have mainly focused on land-use changes induced by urbanization, with comparison between urban and rural stations (Chen et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…By design, reanalysis products do not include in their hindcasting the changes in surface roughness (Thorne and Vose, 2010). Increase of surface roughness can be associated with factors such as urbanization, growth of forests, changes in trees and forest distribution or changes in agricultural practices (Yupeng et al, 2019). Previous studies have mainly focused on land-use changes induced by urbanization, with comparison between urban and rural stations (Chen et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Meanwhile, several studies have also emphasized that the decrease in wind speed was closely related to the change in the surface roughness, which is caused by urbanization, decreases in areas of forestation or pastures, increased vegetation heights due to increased crop production, etc. [ 24 ]. For instance, Zha et al [ 25 ] revealed that the increase in surface roughness could be mainly responsible for a decrement of 0.12 m s −1 for the SWS over China, as well as decreases of 0.57 and 0.30 m s −1 per decade for the wind speed among large and small cities, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zha et al [ 25 ] revealed that the increase in surface roughness could be mainly responsible for a decrement of 0.12 m s −1 for the SWS over China, as well as decreases of 0.57 and 0.30 m s −1 per decade for the wind speed among large and small cities, respectively. Li et al [ 24 ] quantified the surface roughness effects over China during 1979–2015 using the observation-minus-reanalysis (OMR) method and identified an obvious decrease in observed wind speed at a rate of 0.11 m s −1 per decade.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a comparison of urban and rural stations, some studies also used the OMR method to assess the urbanization impact on regional NSWS changes in China (Li et al , 2019. Given that reanalysis products poorly represent many characteristics of historical NSWS changes in many regions (McVicar et al 2008, Pryor et al 2009, Chen et al 2013 as well as existing problems in the rationale of the OMR method (Trenberth 2004, Wang et al 2013, it is advisable to view the OMR-estimated urbanization contribution to the observed regional NSWS trend in urban areas with caution.…”
Section: Comparison Of the Observed And Reanalysis Wind Trendsmentioning
confidence: 99%